Comparison of Bacterial Diversity Between Two Traditional Starters and the Round-Koji-Maker Starter for Traditional Cantonese Chi-Flavor Liquor Brewing - Wang, Jie; Zhong, Qingping; Yang, Yingying; Li, Hanrong; Wang, Li; Tong, Yigang; Fang, Xiang; Liao, Zhenlin (Frontiers in Microbiology, 2018)
Xiaoqu is a traditional fermentation starter that is used for Chinese liquor production. Although microorganisms in the starters are closely associated with the quality and flavour of liquor, knowledge of the microbiota in xiaoqu is still far from complete, let alone the starters produced by new processes. Here, Illumina MiSeq high-throughput sequencing was applied to study bacterial composition in three types of xiaoqu used in Cantonese soybean-flavour (Chi-flavour) liquor, namely two traditional starters (Jiu Bing and Bing Wan) and a Round-Koji-maker starter (San qu) produced by the automatic starter-making disk machine. The results showed bacterial diversity in traditional starters was similar and higher than that in the Round-Koji-maker starter. Lactobacillus and Pediococcus were the dominant genera in all starters, while other different dominant genera also existed in different starters, which were Weissella, Acetobacter, and Gluconobacter for Jiu Bing, Weissella for Bing Wan, and Bacillus, Acetobacter, Acinetobacter and Klebsiella for San qu, respectively. Meanwhile, Cytophagaceae, one particular microbial family, and some pathogens including Klebiella, Crobibacter, and Enterobacter were also found in San qu, indicating the automatic starter-making disk machine should be ameliorated before applied into industrial production. These results enriched our knowledge on xiaoqu-related microorganisms and might be helpful in industrial Chi-flavour liquor production and the development of fermentation technology.